2017
DOI: 10.1177/1747954117694928
|View full text |Cite
|
Sign up to set email alerts
|

Phases in the junior-to-senior transition of Swedish ice hockey players: From a conceptual framework to an empirical model

Abstract: The purpose of this study was to explore a temporal structure (i.e. sequence of phases and relevant psychological content) of the junior-to-senior transition in Swedish ice hockey players. The study was a qualitative exploration of the junior-to-senior transition process designed in three steps. First, the athletic career transition model coupled with a holistic developmental approach and analysis of the Swedish ice hockey context were used to create a conceptual fourphase (preparation, orientation, adaptation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 20 publications
4
45
0
Order By: Relevance
“…When considering the optimal sources of informational support for the JST, research 23 has demonstrated the importance, not only of specialist sport scientists, but also of role 24 models, it being recommend that junior players receive regular opportunities to observe and 25 interact with senior players (e.g. Morris et al, 2015;Stambulova et al, 2017). However, 1…”
Section: Phase 1 Methods 23mentioning
confidence: 99%
See 1 more Smart Citation
“…When considering the optimal sources of informational support for the JST, research 23 has demonstrated the importance, not only of specialist sport scientists, but also of role 24 models, it being recommend that junior players receive regular opportunities to observe and 25 interact with senior players (e.g. Morris et al, 2015;Stambulova et al, 2017). However, 1…”
Section: Phase 1 Methods 23mentioning
confidence: 99%
“…The individual's perception of the transition, the availability of 13 support and their coping skills are all critical factors in the ability to adapt. However, whilst 14 research into the JST reveals the need for significant adjustment, athletes often have limited 15 knowledge of the associated demands, are likely to over-estimate their readiness to cope 16 (Stambulova, Pehrson & Olsson, 2017) and on discovering that they do not have the 17 necessary resources, they may drop out or find themselves in crisis (Stambulova, 2000;18 2017) . 19 For some time, the importance of acquiring such relevant knowledge, the 20 development of coping skills and goal setting to navigate the associated demands, have been 21 acknowledged and demonstrated to be of value at transition (Danish, Petitpas & Hale, 1995), 22 with extensive research at the retirement transition (e.g.…”
mentioning
confidence: 99%
“…The JST begins with increased demands for a junior athlete (e.g. Bruner, Munroe-Chandler, and Spink 2008;Rosier et al 2015;Stambulova, Pehrson, and Olsson 2017), including higher expectations and levels of psychological stress, and higher standards for both practice and performance. Junior athletes are also challenged with the demand to find an optimal life-balance (combining sport with other activities such as education and social life).…”
Section: Athletes' Development From Juniors To Seniorsmentioning
confidence: 99%
“…They differentiate career transitions into normative and non-normative turning points/ phases in the course of a sporting career. Three drastic transitions have been identified and investigated: junior-to-senior transition, transition of student-athletes, and career termination [Vanden Auweele 2004;Vanden Auweele et al 2004;Barker et al 2014;Tokuyama 2015;Pehrson, Stambulova and Olsson 2017;Stambulova, Pehrson and Olsson 2017;Li et al 2018].…”
Section: Athletic Career Explanatory Modelsmentioning
confidence: 99%
“…As Ronda Rousey, Max Schirnhofer, and Yoshihiro Akiyama did. In the qualitative study of Stambulova et al [2017] a conceptual fourphase (preparation, orientation, adaption and stabilization) junior-tosenior transition framework was established. Based on this information an interview guide was constructed.…”
mentioning
confidence: 99%